Abortion in a Mediterranean miniature donkey (Equus asinus) associated with a gammaherpesvirus similar to Equid herpesvirus 7. (November 2015) - LeCuyer, Tessa E.; Rink, Anette; Bradway, Daniel S.; Evermann, James F.; Nicola, Anthony V.; Baszler, Timothy; Haldorson, Gary J.
Fetal tissues and placenta from a third trimester Mediterranean miniature donkey ( Equus asinus ) abortion were submitted to the Washington State University, Washington Animal Disease Diagnostic Laboratory for abortion diagnosis. Microscopic examination of formalin-fixed tissues revealed multifocal necrotizing placentitis. Several cells within the necrotic foci contained large, eosinophilic, intranuclear inclusions. Virus isolation from fresh, frozen placenta identified a cytopathic, syncytia-forming virus. Polymerase chain reaction (PCR) from the cultured virus using degenerate universal herpesvirus primers amplified a 699–base pair portion of the DNA polymerase gene. The PCR amplicon had 96.7% nucleotide identity with the DNA polymerase gene of Equid herpesvirus 7 (EHV-7; asinine herpesvirus 2), a gammaherpesvirus. An identical sequence was obtained when the same degenerate herpesvirus primers were used for PCR on the formalin-fixed placenta. Additionally, the amplicon had complete identity with short sequences of asinine herpesviruses that have been published in association with interstitial pneumonia in donkeys. EHV-7 has previously been isolated from nasal secretions of normal donkeys and mules. Our report describes a case of abortion associated with EHV-7 or a similar virus.